Komparasi Pembuatan Safe Water Garden Sebagai Solusi Sanitasi Di Kampung Bumi Indah, Bintan Dan Desa Nagrak Kabupaten Bandung - Yuana Nurita Umaran; Iwan Juwana (Jurnal Serambi Engineering, 2024)
Wastewater issues in Nagrak Village and Bumi Indah Village where wastewater distribution services are not yet 100% will cause problems for the environment such as unpleasant odors, pollution from substances contained in waste water and causing disease in the community. To overcome problems that often occur, it is necessary to plan a good and appropriate wastewater distribution system so that people do not experience these problems. Safe Water Garden is a wastewater management system that is suitable for small communities such as villages. Not only is the waste water distribution system feasible, but it also provides economic opportunities for the community in Nagrak Village and Kampung Bumi Indah by utilizing domestic waste water produced by the community.